(Computer Vision) - Parikh, Josephine (1990)
Keywords: dept.csc; faculty_collection; sabbatical_report

Application of neural networks to pattern recognition problems in remote sensing and medical imagery - Parikh, Jo Ann; DaPonte, John S.; Damodaran, Meledath; Sherman, Porter (Applications of Artificial Neural Networks, 1990)
The primary objective of this research is the development and testing of neural network models for two fundamental computer vision tasks: edge/line detection and texture analysis. In order to test the ability of the neural network models to detect patterns in images we used both remote sensing data and medical imagery. Neural network models for edge and line detection were used to detect geological lineaments in Landsat data. Neural network models for the analysis of image texture variations were used on ultrasonic images to distinguish patients with normal liver scans from patients with diffuse liver disease. 1.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/084-347-075-228-270, pop00116
Keywords: Artificial Intelligence–Applications; Artificial Neural Networks; Computer Vision; Edge/Line Detection; Imaging Techniques–Medical Applications; Medical Imagery; Neural Networks; Pattern Recognition; Pattern Recognition Systems; Remote Sensing; Texture Analysis; dept.csc